The economic feasibility for commercializing drag reducing agent from cocoa husk - Nabilah, Omor (2013)
The development and application of Drag reduction agent (DRA) mostly related to gas, oil and petrochemical industry. Natural and non toxic DRA is needed to replace existing toxic synthetic polymer and artificial polymers used as flow improvers commercially. Generally, the drag reduction effectiveness of the cocoa husk mucilage was proven, with a maximum percentage drag reduction value of 54.55%.The cocoa bean husk mucilage concentration and the solution flow rate, showed a great effect on profile of drag reduction in the pipe. As concentration of cocoa bean husk mucilage increases, drag reduction increases in all conditions of experimental research. DRA is in demand for refinery industry as flow improver. As for commercialization strategy, 4P’s or marketing mix, 4 P’s stands for Promotion, Place, Price and Product and SWOT analysis were done for DRA. Economic analysis for DRA showing that DRA production is profitable. The DRA is niche player in the specialty and chemical business, focusing on value added product which is not widely or readily available in Malaysia. The operating cost is quite reasonable. The profit of the DRA production plant is quite impressive. Therefore, this plant is believed to be a profit making plant. This DRA production will recover back it capital cost at the 5 year after beginning operation, the DRA would cost just under RM 1.14 or under $1 per barrel of crude oil. DRA product is very unique and highly demand in the market